Improving the lightning performance of overhead lines applying additional underbuilt shield wire - T. Thanasaksiri (2018)
This paper analyzes the lightning performance of 22 kV single and double circuits overhead distribution lines by means of installation the additional underbuilt shield wire. The simulations have been implemented using ATPDraw and calculations by applying equations taken from IEEE std. 1410-2010. The total number of flashovers, direct stroke and induced voltage flashovers, have been evaluated. The additional underbuilt shield wire sizes and the placement locations have been determined. © 2013 IEEE.